A Multilane Traffic Flow Model with Lane Width and the Number of Lanes - Tang, T.; Yang, X.; Wu, Yong Hong; Caccetta, Louis; Huang, H. (IOP Publishing Ltd, 2012)
Based on empirical data, we develop a macro model with lane width and the number of lanes. For uniform flow, the model is formulated as a couple of algebra equations and solved by analytical deduction. The results show that the proposed model can capture the impacts of lane width, the number of lanes and the variation of the number of lanes on uniform flow.